Bonding Through Language Imitation: Influence of Social Ostracism on Structural Priming. (June 2023) - Li, Heng
This research investigated whether being excluded can increase language imitation and thus lead to a stronger structural priming effect. In Study 1, student participants recalling an experience of social exclusion showed a larger priming effect than those recalling an experience of social inclusion. Employing a larger, more diverse sample, Study 2 set out to conceptually replicate Study 1 by creating a concurrent experience of social exclusion through a computerized ball-toss game. It was found that excluded individuals demonstrated a stronger tendency to mimic the syntactic structure used by their interactional partner than included individuals. Taken together, these findings enrich an emergent stream of research that finds structural priming is not an independent cognitive process, but conditioned by various socio-cognitive factors.